2021
DOI: 10.3390/molecules26247597
|View full text |Cite
|
Sign up to set email alerts
|

Composite Fiber Spun Mat Synthesis and In Vitro Biocompatibility for Guide Tissue Engineering

Abstract: Composite scaffolds are commonly used strategies and materials employed to achieve similar analogs of bone tissue. This study aims to fabricate 10% wt polylactic acid (PLA) composite fiber scaffolds by the air-jet spinning technique (AJS) doped with 0.5 or 0.1 g of zirconium oxide nanoparticles (ZrO2) for guide bone tissue engineering. ZrO2 nanoparticles were obtained by the hydrothermal method and characterized by X-ray diffraction (XRD) and scanning electron microscopy (SEM). SEM and fourier-transform infrar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
(54 reference statements)
1
3
0
Order By: Relevance
“…According to Osorio-Arciniega et al, the critical parameter of the scaffold such as physical, chemical, and surface topography properties can induce cellular recognition signals. Their results showed well attachment of hFOB cells to the polylactic acid/zirconium oxide fiber composite with very spreading, elongated, and lamellae morphology [30]. Our study found that the morphology of the BTCP-AE-FM nanocomposite demonstrated an excellent surface for the attachment of DPSCs as is shown in an SEM image.…”
Section: Discussionsupporting
confidence: 66%
“…According to Osorio-Arciniega et al, the critical parameter of the scaffold such as physical, chemical, and surface topography properties can induce cellular recognition signals. Their results showed well attachment of hFOB cells to the polylactic acid/zirconium oxide fiber composite with very spreading, elongated, and lamellae morphology [30]. Our study found that the morphology of the BTCP-AE-FM nanocomposite demonstrated an excellent surface for the attachment of DPSCs as is shown in an SEM image.…”
Section: Discussionsupporting
confidence: 66%
“…It is also noteworthy that the ZrO 2 improve cellular performance and increase hydrophobicity of PLA without affecting their mechanical properties. 432 Arciniega et al 433 used the air-jet spinning technique (AJS) to fabricate PLA/ ZrO 2 fibers of a diameter 395 nm. The surface topography provides a microenvironment that support cell bioactivity and mineral deposits.…”
Section: Zirconia (Zro 2 ) Npsmentioning
confidence: 99%
“…Electrospinning (ES) [ 6 ] and the air-jet spinning technique (AJS) [ 7 ] are the most relevant techniques for the preparation of PLA fibres. Pinese et al [ 6 ] combined the ES process with chemical crosslinking to prepare nanofibers resistant to degradation.…”
mentioning
confidence: 99%
“…Most importantly, the obtained materials exhibit acceptable biocompatibility with murine and mouse fibroblasts cells lines that predispose their application in biomedicine. Alvarez-Perez et al [ 7 ] use the AJS technique to develop nanocomposite fibre scaffolds for tissue bone regeneration. The first step towards this aim was the synthesis of ZrO 2 NPs by the hydrothermal method.…”
mentioning
confidence: 99%